Impact of COVID-19 on athlete mental health - Strategies to promote emotional wellness - Bird, S. P. (International Journal of Strength and Conditioning, 2021)
Recently, I have been heavily involved in discussions with my international colleagues and research teams from New Zealand, Europe, Canada, and United States, around identifying key strategies, solutions and protocols for elite basketball organizations following the unprecedented circumstances and challenges presented by Coronavirus disease (COVID-19). Our discussions have centred specifically on two key areas of player health and wellbeing, those being: (1) the potential mental health challenges faced by coaches, players and support staff, due to quarantine and isolation demands of the unique, yet unknown "NBA bubble"; and (2) the overall impact of COVID-19 and the NBA bubble on player health and wellbeing, in the context of `emotional wellness`.